(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the difference of Downe score between CPAP success and CPAP failure in neonates with respiratory distress. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Neonatal Intensive Care Unit of Recep Tayyip Erdogan Hospital, Muzaffar Garh, Punjab, Pakistan for three months from March 2022 to 31 May, 2022. Materials and Methods: Two groups, each of 30 patients presented with respiratory distress within 24 hours of birth, were made. One group include patients which were successfully treated with CPAP, 2nd group include CPAP failure patients. Results: The Downe score of patients with CPAP failure group was higher compared to those with CPAP failure. Most of the patients with initial Downe score of 5 was successfully treated with CPAP, while those with 7and 8 score failed to improve with CPAP. Downe score more than 6 significantly effects the outcome of CPAP. Conclusion: Initial Downe score is independent predictor of outcome of CPAP treatment in neonates with respiratory distress syndrome. Higher the value increases the risk of failure of CPAP treatment